Leaching studies for metals recovery from printed circuit boards scrap - Oliveira, Paula C. (2010)
In this paper, the leaching behavior of the major metals present in printed circuit boards waste is evaluated, aiming at its recycling by hydrometallurgy. Several leachants were compared (sulfuric, hydrochloric and nitric acids, at 2 M H+ concentration), at temperatures of 25ºC and 90ºC and 4 hours of reaction time. Sulfuric acid leaching was not very promising concerning metals dissolution being only effective for iron. Hydrochloric acid allowed the leaching up to 60% of tin and about 50% of lead, as well as the iron. Nitric acid was the most efficient leachant due to its oxidizing properties. Recoveries of 90% or more for copper, iron, nickel and zinc were achieved at the higher temperature. Lead was also dissolved (up to 80%), as well as silver (more than 70%). These results show that the hydrometallurgical recovery of most of the metals present in PCB’s scrap is a technically feasible alternative that shall be considered and evaluated.